Supporting the enterprise collaboration (EC) and enterprise interoperability (EI) solution benefits by end-user involvement. (26th December 2012) - Karvonen, Iris; Conte, Marco
The paper focuses on creating the prerequisites for taking enterprise interoperability and collaboration solutions into use in supply chains, collaborative networks and business ecosystems. To achieve the expected business benefits, technical implementation is not sufficient; organisational activities are also needed. Software service usability, collaboration maturity, participatory development and a take-up process are seen as requirements for end-user success. The paper discusses the challenges of inter-organisational implementation from the end-user's viewpoint. The focus is on involving the end-users in the development, increasing solution usability and developing guidelines for the take-up process. The paper is based on the work and developments of the COIN project (EU FP7 ICT 216256, see